A Pragmatic Analysis of Implicatures in Covid-19 Coronavirus English Jokes: A Neo-Gricean Approach - Salman, Sahira Mousa; AlSaidi, Abdali H.; Rashid, Sabariah Hj Md (Al-Adab Journal, 2022)
The present study aims at examining implicature in covid-19 Coronavirus jokes in the light of a neo-Gricean approach. For carrying out a meaningful analysis of jokes, an eclectic model is adopted. The data of the study consist of (25) electronic coronavirus English jokes. Only (10) are selected for data analysis. The analysis deals with jokes in terms of their types, principles breaking, and humor devices utilized to infer the meaning of the intended implicature. The jokes are analyzed according to Horn’s (1989/2004) neo-Gricean principles and Attardo’s (1997) Neo-Gricean distinction between two levels of cooperation: the illocutionary Cooperative Principle (ICP) and the Perlocutionary Cooperative Principle (PCP). A neo-Gricean type of principles breaking is conducted by adopting Thomas (1995). While humour devices are analyzed according to Dynel (2009). The data of the study were collected from WhatsApp, Facebook and some other network sources.Data analysis revealed that the (Quantity) Principle is more frequently broken than the (Relevance) Principle. The analysis showed that the ‘violation' of principles was more utilized type of breaking. In addition, ‘flouting’ and ‘opting out’ were also utilized in coronavirus jokes. As for humour devices, ‘sarcasm’, ‘irony’, ‘teasing’, and ‘self-denigrating’ were mostly used in Coronavirus jokes. This indicated that the major concern of the joke teller is criticism through humour.